Spot Moiré Fringes: Determination of Domain Boundaries and Structural Parameters in Ordered Nanoporous Structures. Issue 8 (27th January 2014) - Wang, Qinghua; Kishimoto, Satoshi; Jiang, Xiangfen; Yamauchi, Yusuke
Abstract Spot moiré fringes are generated by the superposition between a nanoporous structure and a digital three‐way grating. The spot moiré fringes are useful for the characterization of the domain boundaries and structural parameters in ordered nanoporous materials. The pitches and the orientations of the nanopore arrays in three directions can be simultaneously determined in a large view field.